Self-Consciousness and Social Interaction Anxiety among School Students of Co-educational and Non-coeducational Schools of Lahore - Zoha Maqsood, Asma Majeed, Israh Anwar (PJE, 2023)
The study aims at identifying a one-to-one correspondence among selfconsciousness and social interaction anxiety between students. Furthermore, the differences between coeducational and noncoeducational schools were also studied. Correlation research design and purposive sampling strategy was used to collect the data. A total sample of N= 200 participants were selected out of which 100 students were enrolled in coeducational, boys and girls, each (n= 50) and 100 participants who were enrolled in non-coeducational schools, boys and girls, each (n= 50) with ages ranging between 14-19 years old. The scales used in the research were The Self-Consciousness Revised Scale (Scheier & Carver, 1985) and Social Interaction Anxiousness Scale (Leary, 1983). Results suggested strong correlation among selfconsciousness both in public and private, as well as in social anxiety and social interaction anxiety. Moreover, no differences were found in relation to the self-consciousness and social interaction anxiety between the students enrolled both within coeducational and non-coeducational schools.